(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Tourism is a very complex phenomenon that involves various ecological, economic, social and cultural aspects, as well as various actors (tourists, residents, authorities and institutions) and where generally little attention has been paid to social and cultural aspects. of this phenomenon, that is to say that the people who have been little noticed are the local people with their history and their specific social and cultural conditions, and who are ultimately the ones who give concreteness to the theoretical approach. The need to develop this marketing study arises from the need to increase the tourist influx to the eco-tourist centers of the municipality of La Trinitaria since they have a great environmental wealth, to better understand the potential and generate market strategies, a descriptive methodology to identify the key success factors of the centers, which was supported by a collection of information with field work, doing this 4 of the main eco-tourist centers of the indicated municipality with the end of obtaining results in the definition of strategies That will help you to be more competitive and obtain economic benefits from the increase in tourist demand.